Acclimatization contributes to stable anaerobic digestion of organic fraction of municipal solid waste under extreme ammonia levels: Focusing on microbial community dynamics. (August 2019) - Yan, Miao; Fotidis, Ioannis A.; Tian, Hailin; Khoshnevisan, Benyamin; Treu, Laura; Tsapekos, Panagiotis; Angelidaki, Irini
Highlights: Ammonia levels up to 8.5 g NH4 + -N/L didn't inhibit anaerobic digestion of OFMSW. Methanogenic dominance shifted from M. concilii to M. soligelidi. M. soligelidi shifted its metabolism to convert H2 /CO2 to CH4 above 7 g NH4 + -N/L. M. concilii 2 is affected negatively from increasing acetate and ammonia levels. Synergistetes and Bacteroidetes were vulnerable to ammonia despite acclimatization. Abstract: The organic fraction of municipal solid waste (OFMSW) is an abundant and sustainable substrate for the anaerobic digestion (AD) process, yet ammonia released during OFMSW hydrolysis could result in suboptimal biogas production. Acclimatized ammonia tolerant microorganisms offer an efficient way to alleviate ammonia inhibition during AD. This study aimed to achieve an efficient AD of OFMSW under extreme ammonia levels and elucidate the dynamics of the acclimatized microbial community. Thus, two mesophilic continuous stirred tank reactors (CSTR), fed only with OFMSW, were successfully acclimatized up to 8.5 g NH4 + -N/L, and their methane yields fluctuated <10%, compared to the methane yields without ammonia addition. Microbiological analyses showed that Methanosaeta concilii and Methanosarcina soligelidi were the dominant methanogens at low and high ammonia levels, respectively. Whilst, a unique metabolic pathway shift, from aceticlastic to hydrogenotrophic methanogenesis, of M. soligelidi was identified during the acclimatization process.